2007
DOI: 10.1111/j.1365-246x.2007.03330.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the pole tide gravimetric factor at the chandler period through wavelet filtering

Abstract: SUMMARY Wavelet analysis for filtering is used to improve estimation of gravity variations induced by Chandler wobble. This method eliminate noise in superconducting gravimeter (SG) records with bandpass filters derived from Daubechies wavelet. The SG records at four European stations (Brussels, Membach, Strasbourg and Vienna) are analysed in this study. First, the earth tidal constituents are removed from the observed data by using synthetic tides, then the gravity residuals are filtered into a narrow period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The gravity effect induced by the ocean pole tide is calculated on the basis of an equilibrium ocean pole tide . Recent results for 4 European stations (Brussels, Membach, Strasbourg, Vienna) given by Hu et al (2007) show the advantage of wavelet filtering in the estimation of the pole tide gravimetric factor at Chandler period. In this study, the atmospheric gravity effect is calculated with a frequencydependent admittance with station air pressure observations.…”
Section: Introductionmentioning
confidence: 98%
“…The gravity effect induced by the ocean pole tide is calculated on the basis of an equilibrium ocean pole tide . Recent results for 4 European stations (Brussels, Membach, Strasbourg, Vienna) given by Hu et al (2007) show the advantage of wavelet filtering in the estimation of the pole tide gravimetric factor at Chandler period. In this study, the atmospheric gravity effect is calculated with a frequencydependent admittance with station air pressure observations.…”
Section: Introductionmentioning
confidence: 98%
“…Thanks to these characteristics, long period gravity tides have been determined (Ducarme et al, 2004;Boy et al, 2006;Hu et al, 2006;Harnisch and Harnisch, 2006), and the gravity pole tide has also been observed (Hinderer and Legros, 1989;Boy et al, 1998;Loyer et al, 1999;Xu et al, 2004;Ducarme et al, 2006;Hu et al, 2007). The gravity pole tides are the gravity variations induced by polar motion of the Earth, which almost entirely consists of the annual wobble (AW) and the Chandler wobble (CW) that has a period of approximately 14 months.…”
Section: Introductionmentioning
confidence: 98%
“…Different analyses of the same data set of polar motion give different results: the CW period may be single, double, multiple, or variable in time. Since that paper has been published, new analyses have been made (Guo et al 2005b; Hu et al 2007; Pan 2007) but no definite conclusion has been reached yet.…”
Section: Introductionmentioning
confidence: 99%